PROBLEMS OF ESTABLISHING NORMS, REVEALING BLANKET CONTENTS OF DISPOSITIONS OF ART. 271-275 OF THE CRIMINAL CODE OF UKRAINE - Taran, Olena V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: the task of scientific research is to determine the specifics of the use of art. 271-275 of the Criminal Code of Ukraine, containing blanket disposition. The system of branch legislation is considered and the limits of its use are defined. Methods: optimization of enforcement of the norms of the Criminal Code of Ukraine, which provide for responsibility for crimes against safety of production. Results: levels of legal regulation and safety of production are defined, which is important for establishing the elements of crimes, provided in art. 271-275 of the Criminal Code of Ukraine. Discussion: international regulatory enactments, national legislation relating to the safety of production and labor protection.